An in Vitro and in Vivo Study of the Effect of Dexamethasone on Immunoinhibitory Function of Induced Pluripotent Stem Cell-Derived Mesenchymal Stem Cells. Issue 9 (September 2018) - Wang, Dan; Sun, Yue-Qi; Gao, Wen-Xiang; Fan, Xing-Liang; Shi, Jian-Bo; Fu, Qing-Ling
Induced pluripotent stem cell-derived mesenchymal stem cells (iPSC-MSCs) represent a promising cell source for patient-specific cell therapy. We previously demonstrated that they display an immunomodulatory effect on allergic airway inflammation. Glucocorticoids are powerful anti-inflammatory compounds and widely used in the therapy of allergic diseases. However, the effect of glucocorticoids on the immunomodulatory function of iPSC-MSCs remains unknown. This study aimed to determine the effect of dexamethasone (Dex) on the immunomodulatory function of iPSC-MSCs in vitro and in vivo. A total of three human iPSC-MSC clones were generated from amniocyte-derived iPSCs. Anti-CD3/CD28-induced peripheral blood mononuclear cell (PBMC) proliferation was used to assess the effect of Dex on the immunoinhibitory function of iPSC-MSCs in vitro. Mouse models of contact hypersensitivity (CHS) and allergic airway inflammation were induced, and the levels of inflammation in mice were analyzed with the treatments of iPSC-MSCs and Dex, alone and combined. The results showed that Dex did not interfere with the immunoinhibitory effect of iPSC-MSCs on PBMC proliferation. In CHS mice, simultaneous treatment with Dex did not affect the effect of iPSC-MSCs on the inflammation, both in regional draining lymph nodes and in inflamed ear tissue. In addition, co-administration of iPSC-MSCs with Dex decreased the local expression of interferon (IFN)-γ and tumor necrosis factor (TNF)-α in the ears of CHS mice. In the mouse model of allergic airway inflammation, iPSC-MSC treatment combined with Dex resulted in a similar extent of reduction in pulmonary inflammation as iPSC-MSCs or Dex treatment alone. In conclusion, Dex does not significantly affect the immunomodulatory function of iPSC-MSCs both in vitro and in vivo. These findings may have implications when iPSC-MSCs and glucocorticoids are co-administered.